Chemical Analysis and Shelf Life Estimation of Rose Flower Tea With Variation of Drying Time - Damayanti, Rofita Eka; Nalawati, Ara Nugrahayu; Setiawan, Andika Putra (International Applied Science, 2024)
Roses from Karangpring Village are a mainstay of Jember Regency and are widely used as sowing flowers. In addition to sowing flowers, roses can also be processed into various processed products such as tea bags, rose jam, candy agar. In making rose tea, the drying process greatly affects the quality and chemical content of the tea. This study aims to determine the effect of temperature variation and drying time on chemical characteristics, organoleptic test, and shelf life of rose flower tea. The materials used were rose flowers, DPPH solution, ethanol, distilled water, amylum solution, ascorbic acid, gallic acid, Na2CO3 7.5%, Follin-Ciocalteu, KCL, HCL, acetic acid, sodium acetate, AlCl3, quercetin. The main tools used in this study are measuring flask, centrifuge, micro pipette, erlenmeyer, UV-VIS spectrophotometer, oven, cup, balance, vortex tube, test tube. Based on SNI dry tea in packaging 3836: 2013 polyphenol content in tea products has a minimum value of 5.2% and a maximum value of water content of 8.0%, thus the polyphenol content and water content of rose flower tea are included in the category set by SNI dry tea in packaging. The highest water content value was found in the P3 treatment of 0.940%, antioxidant content value of 39.181%, polyphenol content of 32.312 mg GAE/g, anthocyanin content value of 4.713%, vitamin C content value of 29.371%, flavonoid content value of 42.521 mg QE/g. The results of the organoleptic test showed that panelists gave scores to treatment P2 with a drying temperature and time of 60oC for 5 hours, and had a shelf life of 17 days.